How Does Conventional Travel Agent Services Enhance Brand Loyalty? The Relationship Between Customer Experience, Brand Credibility, and Brand Trust - Ni Kadek Reinita Andriyani; Putu Gde Arie Yudhistira (Universitas Airlangga, 2023)
Objective: This study examines the relationship between customer experience and brand loyalty mediated by brand credibility and brand trust. Design/Methods/Approach: Primary data was collected using a questionnaire with a purposive sampling technique. A total of 363 respondents who had used one of the conventional travel agent services in Bali participated in this study. The Partial Least Square Structural Equation Model (PLS-SEM) was used to analyze the data through outer and inner models using SmartPLS 4. Findings: This study discovered that customer experience positively has a direct and indirect impact on brand loyalty with the mediating effect of brand credibility and brand trust. Originality: The existing literature supports the direct influence of customer experience on brand loyalty in various industries. However, no other study has investigated the mediating role of brand credibility and brand trust on the relationship between customer experience and brand loyalty. This comprehensive study filled the gap between customer experience and brand loyalty in travel agent services. Practical/Policy implication: This study offered managerial implication. By considering customer experience a competitive advantage, managers can actively evolve several experiential marketing strategies to cultivate brand credibility and trust to impact brand loyalty.